1977
DOI: 10.3109/03009747709095436
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Sacro-Iliitis: A Comparison between Profile Scanning with the Use of99mTc Pertechnetate and Scintigraphy with99mTc Diphosphonate

Abstract: Comparative evaluation of the sensitivity of 99mTc pertechnetate scanning and of 99mTc diphosphonate scintigraphy in detecting sacro-iliac arthritis (S.I.) was performed in 32 patients with definite S.I., 14 with probable S.I., and 6 with inactive S.I., 14 patients without any evidence of S.I. served as controls. Greater diagnostic accuracy was obtained by 99mTc pertechnetate scanning than with 99mTc diphosphonate scintigraphy in patients with active S.I. in the early stages before radiological changes had bec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
0

Year Published

1980
1980
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 9 publications
2
8
0
Order By: Relevance
“…Our findings are in concordance with the few scintigraphy studies that have so far reported on unilateral sacroiliitis (6, including 104 patients with axial SpA and 36 controls) [7][8][9][10][11][12] . Sensitivities of unilateral sacroiliitis in these studies were low, ranging from 6.3% 10 to 33.3% 12 , while specificities were high, ranging between 89.5% 8 and 94.1% 7 , resulting in a pooled LR of 2.1.…”
Section: Discussionsupporting
confidence: 94%
“…Our findings are in concordance with the few scintigraphy studies that have so far reported on unilateral sacroiliitis (6, including 104 patients with axial SpA and 36 controls) [7][8][9][10][11][12] . Sensitivities of unilateral sacroiliitis in these studies were low, ranging from 6.3% 10 to 33.3% 12 , while specificities were high, ranging between 89.5% 8 and 94.1% 7 , resulting in a pooled LR of 2.1.…”
Section: Discussionsupporting
confidence: 94%
“…AS, ankylosing spondylitis; MLBP, mechanical low back pain; NA, not available.*AS: information about disease duration given in six studies,23 28 34 37 46 48 about gender distribution in nine studies,28 3438 40 46 48 about age given in 10 studies,23 28 3438 40 46 48 and about HLA-B27 in seven studies 23 24 28 35 37 38 47

†Suspected sacroiliitis: information about disease duration given in two studies (mean disease duration 2.3 years53 and 3.8 years46), about gender distribution in five studies,29 42 44 51 53 about age in five studies,29 31 46 51 53 and about HLA-B27 in five studies 24 29 42 50 52

…”
Section: Resultsmentioning
confidence: 99%
“…*AS: information about disease duration given in six studies,23 28 34 37 46 48 about gender distribution in nine studies,28 3438 40 46 48 about age given in 10 studies,23 28 3438 40 46 48 and about HLA-B27 in seven studies 23 24 28 35 37 38 47…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations